Exploring the use of research evidence in health-enhancing physical activity policies. Issue 1 (December 2015) - Hämäläinen, Riitta-Maija; Aro, Arja; van de Goor, Ien; Lau, Cathrine; Jakobsen, Mette; Chereches, Razvan; Syed, Ahmed
Abstract Background The gaps observed between the use of research evidence and policy have been reported to be based on the different methods of using research evidence in policymaking by researchers and actual policymakers. Some policies and policymaking processes may therefore be particularly well informed by research evidence compared to others. The aims of the present article are to explore the use of research evidence in health-enhancing physical activity (HEPA) policies, identify when research evidence was used, and find what other types of evidence were employed in HEPA policymaking. Methods Multidisciplinary teams from six EU member states analysed the use of research evidence and other kinds of evidence in 21 HEPA policies and interviewed 86 key policymakers involved in the policies. Qualitative content analysis was conducted on both policy documents and interview data. Results Research evidence was mostly used to justify the creation of HEPA policies and, generally, implicitly without citation. The policies analysed used many types of evidence other than citable research. The evidence used in HEPA policies was found to fall into the following categories: societal framework, media, everyday knowledge and intuition, research evidence, and other types of evidence. Conclusions Research evidence seems to be the only type of evidence used in policymaking. Competition between the use of other types of evidence and research evidence is constant due to the various sources of information on the Internet and elsewhere. However, researchers need to understand their role in translating research evidence into policymaking processes.